STRATEGI PEMASARAN MANISAN RUMPUT LAUT PADA INDUSTRI âCITARASAKUâ DI KELURAHAN TINGGEDE KECAMATAN MARAWOLA KABUPATEN SIGI - Saputra, Arya; Lamusa, Arifuddin; Sulaeman, Sulaeman (AGROTEKBIS, 2016)
This study aimed to determine best marketing strategies for seaweed candy industry "Citarasaku" in Tinggede Village District of Marawola Sigi. This research was conducted in January â February 2016 with the number of respondents was four people. The tool used to analyze both internal and external factors of the industry âCitarasakuâ was the SWOT. Based on the SWOT analysis, the strategy for marketing the seaweed candy is in the quadrant I (Strengths â Opportunities strategy).Â  The best strategies implemented include (a) utilizing the availability of raw materials for production increases in order to meet highly increasing demand, (b) promoting attractive packages and affordable candy price through various media, (c) maintaining the quallity of the products in order to take advantage of goverment assistance and activities organized by government such as exhibitions.Â Key Words: Candy, marketing strategies and SWOT analysis.